Periampullary localized pancreatic intraepithelial neoplasia-3 (PanIN-3) - Algin, Oktay (Radiology and oncology (Ljubljana), 2011)
Background. The early determination of premalignant lesions of pancreas can prevent unnecessary excessive surgical procedures and can reduce morbidity andmortality. Pancreatic intraepithelial neoplasia-3 (PanIN-3) is a preinvasive form of adenocarcinoma (carcinoma in situ). PanINs have not taken place in the literature of radiology yet, it should be considered in differential diagnosis of pancreatic cystic lesions. Case report. A patient with preliminary diagnosis of chronic cholecystitis who had choledocolithiasisand periampullary pancreatic cyst detected by noncontrast-enhanced (NCE) and contrast-enhanced (CE) magnetic resonance cholangiography (MRCP) is presented. Pathological examination results of gallbladder and pancreatic cyst were reported as gallbladder adenocarcinoma and PanIN-3, respectively. Conclusions. Pancreatic cystic lesions with thin septa which enhances slightly with the administration of contrast material mayrepresent PanIN-3. In patients with cystic pancreatic lesion localized at periampullary region, using CE-MRCP together with NCE-MRCP could be useful in the evaluation of pancreatic cystic masses as well as other abdominal pathologies.
Keywords: Adenocarcinoma; Adenokarcinom; Adult; Carcinoma In Situ; Cholangiography; Diagnosis; Holangiografija; Karcinom in situ; Magnetic Resonance Imaging; Magnetna resonanca; Odrasli; Pancreatic Cyst; Pancreatic Neoplasms; Trebušna slinavka, cista; Trebušna slinavka, novotvorbe